The organelle genomes of the endangered seagrass Zostera caespitosa reveal sequence divergences, massive gene transfer, and uncommon RNA editing types - Yong, Yushun; Wang, Yulian; Wang, Dawei; Yuan, Xingfang; Zhang, Quansheng (Frontiers in Plant Science, 2025)
IntroductionZostera caespitosa, a rare submerged angiosperm, is considered endemic to the northwestern Pacific.MethodsThis study assembled and compared the mitochondrial (mt) and chloroplast (cp) genomes of Z. caespitosa to understand the organelle evolutionary patterns.Results and discussionThe cp genome (143,972 bp) was the second smallest within the seagrasses, whereas the mt genomes (192,246 bp) of Z. caespitosa and other seagrasses were smaller compared to those of other monocotyledons. The protein-coding genes (PCGs) in the organelle genome exhibit a strong A/U bias at codon endings, a selection-driven codon bias. The rates of nonsynonymous (Ka) and synonymous (Ks) substitutions in the mt genes of Zostera were two times higher than those in the cp genes. Additionally, 50 mitochondrial plastid DNA (MTPT) segments, totaling 44,662 bp, were identified, constituting 23.23% of the mt genome, which is significantly higher than those in most land plants. Phylogenetic analysis of 13 seagrass core cp-PCGs supported previous studies showing two genera in family Zosteraceae: Phyllospadix and Zostera, the latter comprising Zostera and Zosterella as subgenera. RNA editing was remarkably abundant in the 167 mt-PCGs and 172 in cp-PCGs, particularly in the cp genome. There are 11 different RNA editing types in the cp and 3 in the mt, most of which are C to U. Unexpectedly rare editing events, such as A to C, A to U, U to A, G to C, and U to G, have also been found in the cp.